ANALYSIS OF STUDENT’S SATISFACTION LEVEL TOWARDS LEARNING METHODS OF LECTURERS IN INDUSTRIAL REVOLUTION 4.0 : A SURVEY OF HIGHER STUDENT IN FIRST SEMESTER - Dewi Natalia Marpaung (Steam Engineering, 2021)
This study aims to analyze the level of student satisfaction on learning methods that conducted by lecturers who teach in industrial revolution 4.0 era, especially higher student first semester at Musamus University. The data obtained from 120 respondents first semester students, spread across several majors in Musamus University. This research is a quantitative descriptive study which uses a questionnaire for data collection which is carried out through online survey. Data tabulation is calculated using a Likert scale to obtain a percentage of student satisfaction levels. The results obtained are a relationship between student satisfaction with the learning methods carried out by lecturers in terms of time discipline, mastery of the material, delivery of material, assessment and evaluation during the lecture process. The results of the analysis of the performance of lecturers perceived by students of the satisfaction t in the era of learning industry 4.0 through learning methods carried out from various aspects and factors in the lecture process have a positive effect. Total average from three indicators are 81% categorized student satisfied for learning method yhat conducted by lecturer in Musamus university but still need to improve for evaluation and assessment.